168k views
2 votes
I really need help with this

I really need help with this-example-1
User MAG
by
5.1k points

1 Answer

3 votes
1. 4x=7(x-3) -----> Start with the given.
2. 4x=7x-21 -----> Distribute 7 by multiplying it to the individual terms inside the parenthesis. 7(x) - 7(3) = 7x -21
3. -3x=-21 ------> From step 2, combine like terms by transposing. The equation becomes 4x - 7x = -21. Simplifying, it becomes -3x = -21
4. x = 7 -----> Divide both sides by -3, you get the value o x.
User Abdurrahim
by
5.5k points